Rumen modulatory effect of thyme, clove and peppermint oils in vitro using buffalo rumen liquor - Roy, Debashis (Vet World, 2015)
AIM: The present study was conducted to examine the rumen modulatory effect of thyme, clove and peppermint oils on rumen fermentation pattern in vitro using roughage based diet. MATERIALS AND METHODS: Thyme, clove and peppermint oils were tested at concentration of 0, 30, 300 and 600 mg/l (ppm) of total culture fluid using in vitro gas production technique in wheat straw based diet (concentrate: Wheat straw 50:50). Different in vitro parameters e.g., total gas production, methane production, nutrient degradability, volatile fatty acid (VFA) production and ammonia nitrogen concentration were studied using buffalo rumen liquor. RESULTS: Thyme oil at higher dose level (600 ppm) reduced (p<0.05) total gas production, feed degradability and ammonia nitrogen (NH(3)-N) concentration whereas total VFA concentration was significantly lower (p>0.05) in 300 and 600 ppm dose levels. 600 ppm dose level of clove oil reduced (p<0.05) total gas production, feed degradability, total VFA and acetate to propionate ratio. Methane production was significantly reduced (p<0.05) in 300 and 600 ppm dose levels of clove and peppermint oil. CONCLUSION: Right combination of these essential oils may prove to enhance performance of animals by reducing methane production and inhibiting protein degradation in rumen.